2014
DOI: 10.1088/0953-8984/26/27/275401
|View full text |Cite
|
Sign up to set email alerts
|

Predicting failure: acoustic emission of berlinite under compression

Abstract: Acoustic emission has been measured and statistical characteristics analyzed during the stress-induced collapse of porous berlinite, AlPO4, containing up to 50 vol% porosity. Stress collapse occurs in a series of individual events (avalanches), and each avalanche leads to a jerk in sample compression with corresponding acoustic emission (AE) signals. The distribution of AE avalanche energies can be approximately described by a power law p(E)dE = E(-ε)dE (ε ~ 1.8) over a large stress interval. We observed sever… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 39 publications
8
29
0
Order By: Relevance
“…Experimentally, it has been shown that the avalanches stem from sudden changes of the internal strain field (displacement discontinuities), which usually lead to shrinking of the sample and can be detected by measuring the acoustic emission (AE) originating from contraction. Avalanche behavior has been observed previously in porous Vycor glass [10], natural goethite [11], porous alumina [12], and berlinite [13]. Their statistical characteristics share many similarities with seismicity such as the Earth crust failure due to stresses originated from plate tectonics [14,15].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Experimentally, it has been shown that the avalanches stem from sudden changes of the internal strain field (displacement discontinuities), which usually lead to shrinking of the sample and can be detected by measuring the acoustic emission (AE) originating from contraction. Avalanche behavior has been observed previously in porous Vycor glass [10], natural goethite [11], porous alumina [12], and berlinite [13]. Their statistical characteristics share many similarities with seismicity such as the Earth crust failure due to stresses originated from plate tectonics [14,15].…”
Section: Introductionmentioning
confidence: 68%
“…Nevertheless, the corroboration of this hypothesis certainly requires more detailed investigations. The behavior in SiO 2 -porous materials is different from other porous materials such as goethite [11], berlinite [13], or alumina [12], which are also granular materials.…”
Section: Discussionmentioning
confidence: 93%
“…In this context, we mention insightful laboratory experiments on porous rocks using microtomography, which show evidences of nucleation and propagation of precursory deformation and of self-organization of porosity prior to catastrophic failure 10 . Other 'labquake' experiences determined precursors of failure by measuring the acoustic emission of rock samples under compression 11 , finding that in sufficiently porous materials an increase of energy emission occurs near failure. This led to the proposal of using pico-seismicity detection of foreshocks for the prediction of mine collapses in highly porous environments.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of how to predict material strength and sample failure is where engineering, materials science, and physics meet [1][2][3][4]. The predictability of lifetimes of structures and materials involves phenomena on various scales, beginning with atomic interactions.…”
Section: Introductionmentioning
confidence: 99%